Evidence-Based Medicine and the Potential for Inclusion of Non-Biomedical Health Systems: The Case for Taijiquan - Langweiler, Mark J. (Frontiers in Sociology, 2021)
The world is becoming a much smaller place. Immigration and the use of information technology has brought us closer together. One aspect of this is the availability of non-traditional (by Western standards) health systems. Many of these systems, such as Traditional Chinese Medicine including tai chi chuan, Ayurvedic or acupuncture, are easily found in many North American and European cities. For the most part these practices are not accredited, and their validation remains limited. This is primarily the result of the lack of modern scientific research of them. Additionally, the studies that are preformed rely on evidence and research designs that often negate the true features of these practices with a loss of authenticity. Is it possible or even desirable for these systems to acquire accreditation and inclusion? If so, given the apparent, subjective nature of these practices, can a pluralistic approach to healthcare that retains the Western values of science and medicine and yet respects the diversity of different concepts about life, health and services be developed while permitting these practices to maintain their authenticity? And is it possible to develop a regulatory framework that practitioners can use? The current paper will examine these and related questions concerning the uses of non-Western healthcare practices without the loss of their authentic nature. Using the inclusion of tai chi chuan as a health promoting martial art as the model, the process of integration will be examined.